Interpretasi Pendidikan Karakter Anak dalam Al-Qur'an - Ahmad Zabidi; Sri Sunantri; Hamnah (Jurnal Ilmiah Edukatif, 2023)
With its function as a guide for humans, Muslims from generation to generation have tried to understand the contents of the Koran and convey the results of this understanding in various studies which aim to serve as reference material for Muslims as well as in efforts to make the Qur'an a guide in his life. Because the Qur'an has an important position in Islamic studies, apart from functioning as a guide, the Qur'an functions as a Furqan (differentiator), namely being a benchmark and differentiator between what is haq and what is false. The research method used in this research is qualitative with a literature review type of research. Primary data sources used were several research journals and books related to the interpretation of children's character education in the Koran. The data analysis technique uses content analysis. The results of the research state that the interpretation of children's character education in the Al-Qur'an is the main capital in forming children's character education with integrity, morals and good character. The interpretation of children's character education in the Qur'an provides a good picture, guideline and role model for family life which is the basic capital in forming a child's personality that is pious and pious and devoted to both parents and can interact and communicate well with fellow humans.